Termination of a Criminal Case (Criminal Prosecution) Due to the Imposition of a Court Fine - Volevodz, Alexander; Ivanov, Dmitriy; Polyakov, Sergey; Bezryadin, Viktor; Alyshkin, Vladislav (Jurnal Cita Hukum, 2023)
Criminal cases in Russia often hinge on a critical decision during the preliminary investigation stage: whether to proceed to trial or terminate the case. While various grounds for termination exist, one central condition revolves around the compensation or reparation for harm caused by the crime. This article examines the termination of criminal cases through court fines to compensate for the damage caused by crimes. The research utilizes the general scientific method of cognition for detailed examination and analysis, the systematic approach method for procedural considerations, and methods of analysis and synthesis to identify law enforcement challenges. The study systematically analyses the legal provisions and judicial practices related to imposing court fines since 2016. Results indicate that total compensation for harm is crucial for applying termination grounds under Article 25.1 of the Criminal Procedure Code. Voluntary harm compensation often leads to the termination of criminal cases, effectively preventing the creation of a criminal record for the accused.